O necropolă medio-bizantină cercetată la Nufăru, jud. Tulcea, punctul Trecere bac. Consideraţii arheologice preliminare - Damian, O.; Vasile, M.; Samson, A. (Materiale și Cercetări Arheologice)
The authors present the results of an archaeological investigation in a Middle Byzantine fortress, settlement and necropolis, overlapped by the present-day village of Nufăru, Tulcea County. The investigated area is placed on the northern part of a rocky hill (Trecere bac). A part of the northern inner wall and the wharf of a Middle Byzantine fortress, two habitation layers, with dwellings and garbage pits, and 450 graves were discovered in the course of the excavations (1999– 2002, 2004– 2014, 2016). A large number of the graves were disturbed, and only 215 were relatively well preserved and made it possible to determine the orientation of the body and the position of the heads, arms and legs. All burials in the necropolis were performed in accordance with the Christian burial rites – by inhumation in extended position, the head oriented to the west and the feet to the east, with a certain seasonal deviation in the orientation. The most frequently occurring grave in the necropolis was the simple rectangular pit. In some of the burials the bodies were entirely or, more often, partially surrounded with broken or flat stones, especially the heads and the lateral parts of the skeleton. The inhumation in crypts, excavated in the rock, is also registered (10 situations). Burials in coffins – preserved by scarce traces of wood and nails and other iron elements – were also found in the cemetery. Another peculiarity in the burial ritual observed in the necropolis, was the placing of the head of the deceased on a flat stone or on a brick or a tile. The graves in the necropolis did not have any marking. This is also evidenced by the overlapping burials, demonstrating a remarkable density inside the graveyard. There were also relatively frequent cases when the pit of a burial cut the pit of an earlier one, but in only 45 situations was noticed a care for the disturbed remains, which were partially gathered and placed next to the body of the newer burial, like a secondary burial / re-inhumation. During the excavations, there appeared cases when one or several graves were stratigraphically overlying destroyed earlier dwellings, or were overlapped/ disturbed by garbage pits. The position of the forearms of the deceased reveals several variants : stretched close to the body, crossed over the chest, the abdomen or the pelvic area, bent next to the shoulder. The legs were generally parallel, more or less close together, in several cases flexed on one side or the other, with the tibiae or the femurs overlapping in an “ X” shape. The deceased were probably buried (67 cases) only with the articles of adornment (for the head, for the neck, and for the hands / arms – bronze and silver earrings, necklaces of beads made of bone, glass, amber and of a tropical shell Cyprea, bronze finger rings, bronze and glass bracelets), and clothes’ accessories (bronze buckle and buttons) belonging to them. Small bronze and amber crosses, bronze crosses-encolpions were also discovered as grave goods. The coins discovered in several graves reveal the fact that the inhabitants of the settlement were also familiar with the custom of „ Charon’s obols”. The necropolis investigated at Trecere bac, dating from the end of the 11th century to the beginning of the 13th century, is the most important funerary area in the archaeological site of Nufăru, Tulcea County, and one of the Christian graveyards of Middle Byzantine Dobrudja